The Effectiveness of Flipped Classroom Strategy on Self-Directed Learning Among Undergraduate Mathematics Students - Mohd Nasir, Mohd Azrin; Alaudin, Ros Idayuwati; Ismail, Suzilah; Mat Ali, Nor A’tikah; Mohd Faudzi, Farah Nadia; Yusuff, Noraini; Mohd Pozi, Muhammad Syafiq (UUM Press, 2020)
The purpose of this study is to measure the effectiveness of the flipped classroom strategy for self-directed learning among undergraduate students in Mathematics courses. A forty-six (46) students of Actuarial Mathematics course from one university were participated to measure their academic performance during-the-class. A six number of students were randomly selected for a survey with open-ended questions via google form to explore their experiences using this approach. For this study, there was a pre-experimental research design with a group of students in one class. There were two ways of teaching techniques to make a comparison in this study. First, the undergraduate students were taught using a traditional teaching method to provide a baseline, where the instructor showed and explained all the steps to solve mathematical problems, and the understanding of the students will be assessed by conducting a pre-assessment quiz. Second, the students were taught using flipped classroom strategy, where the students were given the solutions including all the steps to solve mathematical problems without guidance or explanation from the instructor, then the students were given similar mathematical problems to be solved by themselves by referring to the example given, then the understandings of students will be assessed by conducting a post-assessment quiz. Third, reimplementing the flipped classroom strategy by conducting the third quiz. Finally, the effectiveness of the flipped classroom strategy is measured by comparing the results from all assessment performance. Also, teacher reflection and students’ feedback were gathered to access self-directed learning effectiveness. The result showed that the post-assessment performance from a flipped classroom strategy was significantly higher than the pre-assessment performance from traditional teaching methods. The lowest score of the pre-assessment using the traditional teaching method was less than one (1) score. On the contrary, the lowest score of the post-assessment performance using the flipped classroom strategy was five (5) scores. Moreover, the majority of the respondents achieved eight to ten scores. From the result, it was found that both teaching methodologies produced different results in students’ performance for this study. Besides, the students also provided good feedback from the strategy based on the result of the interview: (a) fun and interesting, (b) curiosity, (c) providing students’ autonomy, (d) initiating communication, (e) integrating the use of technology in learning mathematics, (f) preparing for the final exam. Overall, the students found that the flipped classroom strategy is potentially enhancing student’s engagement and performance in mathematics education. The findings have implications for the instructors to implement the flipped classroom strategy for mathematics subjects to acquire better performance among undergraduate students. The flipped classroom requires self-directed learning among students that can be more interesting learning experiences among the students